Pemberian Edukasi Tentang Persiapan Pemberian ASI Pada Ibu Hamil Trimester III Melalui Media Leaflet - Siti Maria Ulfa; Pratiwi Puji Lestari (CV. Multi Kreasi Media, 2024)
The third trimester of pregnancy is a crucial phase in preparation for birth, where the fetus and mother experience significant growth. After going through the birthing process, mothers enter the postpartum period which is full of challenges, including preparation and implementation of breastfeeding. The postpartum period is not only about physical recovery, but also psychological and emotional adjustment to a new role. This community service activity aims to provide adequate understanding to third trimester pregnant women regarding preparation for breastfeeding. Through outreach using leaflets as a medium of information, this activity focuses on the benefits of breastfeeding, correct breastfeeding techniques, handling common problems during breastfeeding, and the importance of family support. Specific objectives include increasing maternal knowledge, emotional support, and involving the family as the main support agent. This activity was carried out at the Banjarmasin City Regional Health Center in March–May 2023, involving 30 third trimester pregnant women. Evaluation is carried out to ensure maximum understanding of the material.